Proposals and recommendations on the methodology of using modern graphic programs in teaching the science of construction drawing - Mardov, Sanjar; Sadykova, Zhanna (Рroblems of engineering and professional education, 2022)
In this article, theoretical data, rules, drawing methods based on the state standard, which is one of the main factors in teaching typing in educational institutions